Targeted deletion of the TSLP receptor reveals cellular mechanisms that promote type 2 airway inflammation - Kabata, Hiroki; Flamar, Anne-Laure; Mahlakõiv, Tanel; Moriyama, Saya; Rodewald, Hans-Reimer; Ziegler, Steven F.; Artis, David (Mucosal immunology, 2020)
Thymic stromal lymphopoietin (TSLP) is a critical upstream cytokine inducing type 2 inflammation in various diseases, including asthma and atopic dermatitis. Accumulating evidence suggests that TSLP can directly stimulate a variety of immune cells, such as dendritic cells (DCs), basophils, T cells, and group 2 innate lymphoid cells (ILC2s). However, which cell types directly respond to TSLP in vivo and how TSLP initiates type 2 inflammation has remained controversial. To define the precise role of TSLP in vivo, for the first time we generated multiple cell lineage-specific TSLP receptor-deficient mice to systematically dissect the cell-intrinsic requirements for TSLP responsiveness in type 2 inflammation in the lung. In papain-induced innate immune-mediated type 2 airway inflammation, TSLP directly stimulated ILC2s, but not basophils, leading to enhanced type 2 inflammation. On the other hand, in OVA-induced adaptive immune-mediated type 2 airway inflammation, TSLP principally acted on DCs and CD4 + T cells during the sensitization phase, but not basophils or ILC2s, and facilitated the development of Th2 cell-mediated airway inflammation. Together, these findings reveal that TSLP activates distinct immune cell cascades in the context of innate and adaptive immune-mediated type 2 inflammation.